Characterization of assemblages in neotropical cave dwelling bats based on their diet, wing morphology, and flight performance - Salgado-Mejia, Fernando; López-Wilchis, Ricardo; Guevara-Chumacero, Luis Manuel; Valverde-Padilla, Pedro L.; Corcuera Martínez del Rio, Pablo; Porto-Ramírez, Sergio L.; Rojas-Mertínez, Ixchel; Samano-Barbosa, Gihovani A. (THERYA, 2021)
Bats have a great variety of wing morphologies that determines the bat’s flight performance, and this in turn conditions the forage aerosphere and the food it can obtain. Several studies have shown differences in wing morphology, flight performance, and forage aerospheres among species from different trophic guilds. However, for species that share a guild this is not entirely clear. It is possible that these species have differences in their diet and show changes in wing morphology that modify their flight performance and forage areas. Determining this will allow a better understanding of spatial segregation among species that share a trophic guild. These studies allow the identification of species assemblages based on wing morphological differences and flight performance that would not be distinguished only by guild membership. Our goal was to define the species assemblages that make up a community of Neotropical cave dwelling bats based on their trophic guild, flight performance, and forage zone. A community of Neotropical cave dwelling bats from a cave in Veracruz, Mexico was analyzed. The diet of each species was determined by means of their stomach contents and bibliographic review. In addition, aspect ratio, wing loading and tip index were calculated. Based on the wing characteristics and diet, multivariate groupings and orders were performed, as well as to define the assemblages present. According to the wing characteristics and the dietary composition, four groups of species were found that represent four different flight characteristics in terms of agility and maneuverability. There was agreement between diet and wing characteristics, and the four trophic groups were identified through canonical correspondence analysis. Correlating wing morphology, diet and forage area allows us to adequately define the assemblages of a community of bats. Regarding the hypothesis, it was found that species that share a food guild show differences in the composition of their food and wing morphology, which generate differences in flight performance and forage areas. Four assemblages differing in forage aerospheres among three trophic guilds are described: understory and facultative artrhopodivorous, semi-clearing hematophages, and facultative nectarivores. Finally, spatial segregation between the species of the families Mormoopidae and Natalidae was recognized.